1999
DOI: 10.1081/ada-100101850
|View full text |Cite
|
Sign up to set email alerts
|

Women Inmates' Risky Sex and Drug Behaviors: Are They Related?

Abstract: The large concentration of female illicit drug users in state correctional facilities prompted an examination of the associations among different types of drug use and sexual risk factors related to human immunodeficiency virus (HIV) among women inmates. A consecutive sample of 805 women felons admitted to the North Carolina Correctional Institution for Women between July 1991 and November 1992 was interviewed. Of these inmates, 651 had complete information on relevant characteristics. Of the women inmates, 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 35 publications
2
46
2
Order By: Relevance
“…This finding is consistent with many studies in the literature that have found that alcohol abuse and illicit drug abuse are independently associated with high risk sexual behavior, and the risk for HIV transmission [45,54]. Substance abusing individuals may engage in higher risk sexual behavior because of impaired decisionmaking while under the influence of substances [10], as well as be more likely to have higher risk sexual partners [6,29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with many studies in the literature that have found that alcohol abuse and illicit drug abuse are independently associated with high risk sexual behavior, and the risk for HIV transmission [45,54]. Substance abusing individuals may engage in higher risk sexual behavior because of impaired decisionmaking while under the influence of substances [10], as well as be more likely to have higher risk sexual partners [6,29].…”
Section: Discussionsupporting
confidence: 91%
“…Rates of unprotected vaginal sex with multiple partners reported by men and women in our study (49.6 and 40.3%, respectively), was lower than the 62% reported for participants in a similar study conducted in four prisons in the State of Illinois, USA (Swartz et al, 2004). The rate of unprotected vaginal intercourse found among men in our study is similar to that obtained among men in three States in the USA (49.6 vs. 45.3%; Seal et al, 2008) and the rate among women is similar to that reported in a previous study (40.3 vs. 35%) (Cotten-Oldenburg et al, 1999). A quarter of the women and 14% of the men in our study reported IDU.…”
Section: Discussionsupporting
confidence: 81%
“…A quarter of the women and 14% of the men in our study reported IDU. Compared with some other studies, IDU was low in our study (Cotten-Oldenburg et al, 1999;Belenko, Shedlin, & Chaple, 2005). In our study, male and female participants who reported inconsistent condom use with multiple anal sex partners were more likely to report the same with multiple vaginal sex partners.…”
Section: Discussioncontrasting
confidence: 74%
“…Numerous studies have found that condom use is more likely with IDUs' nonsteady partners than with primary or steady partners (1,5,6,(8)(9)(10)(11)(12)(13). Additional sexual risk behaviors practiced by IDUs involve exchanging sex for drugs or money, engaging in sexual intercourse with other IDUs, and using alcohol and/or drugs prior to or during sex (8,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Some have assessed drug users' HIV risk behaviors in inpatient treatment, primary care clinics, methadone maintenance programs, and while incarcerated (9,12,15,19). The current study was undertaken to identify differences between IDUs (in a needleexchange program) who report no sexual behavior, those who report sex with one partner, and those who report sex with more than one partner in the past six months.…”
Section: Introductionmentioning
confidence: 99%